Open Science in eating disorders: Using current evidence to inspire a plan for increasing the transparency of our research. Issue 5 (7th January 2023) - Gorrell, Sasha; Cohen, Shira; Schaumberg, Katherine; Anderson, Lisa Marie; Reilly, Erin E.
Abstract: Objective: There is increasing consensus that open science practices improve the transparency and quality of clinical science. However, several barriers impede the implementation of these practices at the individual, institutional, and field levels; understanding and addressing these barriers is critical to promoting targeted efforts in increasing effective uptake of open science. Methods: Within this research forum, we drew from publicly available online information sources to identify initial characterizations of researchers engaged in several types of open science practices in the field of eating disorders. We use these observations to discuss potential barriers and recommendations for next steps in the promotion of these practices. Results: Data from online open science repositories suggest that individuals using these publishing approaches with pre‐prints and articles with eating‐disorder‐relevant content are predominantly non‐male gender identifying, early to mid‐career stage, and are more likely to be European‐, United States‐, or Canada‐based. Discussion: We outline recommendations for tangible ways that the eating disorder field can support broad, increased uptake of open science practices, including supporting initiatives to increase knowledge and correct misconceptions; and prioritizing the development and accessibility of open science resources. Public Significance Statement: The use of open science practices has the potential to increase the transparency and quality of clinical science. This Forum uses publicly sourced online data to characterize researchers engaged in open science practices in the field of eating disorders. These observations provide an important framework from which to discuss potential barriers to open science and recommendations for next steps in the promotion of these practices.